Pemodelan dan Simulasi Beban Non-Linier 3-Fasa dengan Metoda Sumber Arus Harmonik - Rizka Amalia; Refdinal Nazir (Jurusan Teknik Elektro Universitas Andalas, 2015)
The fast technological development in electronics fields leads to the increasing use of non-linear loads in households, offices, industry, or other fields. Harmonic caused by non-linear loads are very unique, which means that each non-linear load produces different nature a characteristcs of the resulting harmonic. Usually, non-linier loads have so complicated equivalent circuit that it is more difficult to describe the nature and characteristic of each non-linier load. Therefore, in order to make the study easier, modeling approach of non-linier loads is needed so that it makes it easier to see the nature and characteristics of them. In this approach, harmonic current wave is used as the base to make simulation model of non-linear load using current source in SIMULINK MATLAB. By using the concept of phase shifted and phase sequences current source are connected in parallel in which each current source represent one harmonic order. From simulation, it is found out that the result is approximately the same as that of laboratory test. The harmonic current wave is the same at phase a, phase b, and phase c, with 120 º shift. Keywords : Self Excited Induction Generator (SEIG), Non-linear load, Harmonic, Total Harmonic Distortion (THD).Abstrak— Perkembangan teknologi dibidang elektronika yang sangat pesat menyebabkan meningkatnya penggunaan beban non-linier, baik di rumah tangga, perkantoran, industi atau bidang lainnya. Harmonisa yang ditimbulkan beban non-linier sangat unik, artinya setiap beban non-linier berbeda sifat dan karakteristik harmonisa yang dihasilkannya. Biasanya beban non-linier memiliki rangkaian ekivalen yang lebih rumit, sehingga lebih sulit di jabarkan untuk tujuan melihat sifat dan karakteristik masing-masing beban non-linier. Oleh Karena itu dibutuhkan kajian pemodelan beban non-linier untuk mempermudah melihat sifat dan karakteristiknya. Pada kajian ini data arus harmonisa menjadi dasar pembuatan model simulasi beban non-linier menggunakan sumber arus pada simulink MATLAB. Dengan menggunakan aturan beda fasa dan urutan fasa sumber arus dirangkai secara paralel, dimana setiap sumber arus mewakili satu orde harmonisa. Dari simulasi yang dilakukan didapatkan hasil yang mendekati hasil pengujian di laboratorium. Gelombang arus harmonisa sama pada fasa a, fasa b dan fasa c hanya saja bergeser 120º.Kata Kunci : Generator Induksi Penguatan Sendiri (GIPS), Beban Nonlinier, Harmonisa,Total Harmonic Distortion (THD).